Bacterial biosynthesis of abietane-type diterpene ferruginol from glucose - Hyun Jeong Lee; Chaeyeon Kim; Yu Been Heo; Seong-Eun Kim; Han Min Woo (Microbial Cell Factories)
Abstract Background Microbial supply of plant extracts is a promising biomanufacturing strategy that requires engineering of metabolic pathways and enzymes. This study presents the engineering of Corynebacterium glutamicum for heterologous production of diterpenes miltiradiene and ferruginol. Results Through targeted metabolic pathway modifications, including inactivation of pyruvate carboxylase and phytoene synthase, the HL01 strain was optimized to enhance pyruvate and geranylgeranyl pyrophosphate (GGPP) pools. Overexpression of key MEP pathway enzymes (Dxs and Idi) and implementation of three GGPP synthase modules further boosted diterpene synthesis. Then, combining those modules with diterpene synthase (DiTPS) and intact P450 reductase modules (CYP76AH1 and CPR1) enabled production of miltiradiene (ferruginol equivalent) at 237.46 ± 34.8 mg/L and ferruginol at 107.34 ± 1.2 mg/L under constant glucose feeding, respectively. Conclusions Modular gene expression for heterologous metabolic pathway can be optimized for bacterial biosynthesis. This is the first demonstration of ferruginol production in bacteria. These findings pave the way for further optimization of diterpene biosynthesis through pathway engineering and module integration in bacterial systems.